Peningkatan Kontras Pada PreProcessing Gambar Permukaan Solar Panel dengan Histogram - wiliani, ninuk; Khawa, Titik; Ramli, Suzaimah (Innotech: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
Contrast enhancement in solar panel surface images is a crucial step to support inspection and defect detection processes, such as cracks, scratches, and stains. This study aims to enhance the visibility of details in solar panel surface images using the Contrast Limited Adaptive Histogram Equalization (CLAHE) method. The evaluation was conducted by comparing visual results, histogram distribution, and image quality measurements. The results indicate that the CLAHE method effectively redistributes pixel intensity more evenly than traditional histogram methods and produces images with better contrast without losing essential information. This enhancement supports the identification of defect characteristics on solar panel surfaces. These findings significantly contribute to the development of image processing technologies for solar panel maintenance and other applications requiring improved visual quality